2020
DOI: 10.2219/rtriqr.61.1_54
|View full text |Cite
|
Sign up to set email alerts
|

<b>Development of a Superconducting Magnetic Bearing Capable of Supporting Large Loads in a Flywheel Energy Storage System for Railway Application</b>

Abstract: Application of the flywheel energy storage system (FESS) using high temperature superconducting magnetic bearings (SMB) has been demonstrated at the Komekurayama photovoltaic power plant located in Yamanashi Prefecture. In order for the FESS to be applied to railways as a system able to prevent cancellation of regenerative braking its storage capacity must be increased. Therefore, levitation force tests up to 158 kN and tests to determine the creep characteristics of the levitation force were carried out to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The radial and axial restoring forces of the SMBs produced in this research were compared with those of models in previous studies [5]. Figure 10 shows the structure of the SMB that we created.…”
Section: Comparison With Previous Research Of the Restoring Force Alo...mentioning
confidence: 98%
See 3 more Smart Citations
“…The radial and axial restoring forces of the SMBs produced in this research were compared with those of models in previous studies [5]. Figure 10 shows the structure of the SMB that we created.…”
Section: Comparison With Previous Research Of the Restoring Force Alo...mentioning
confidence: 98%
“…Figure 10 shows the structure of the SMB that we created. The HTS used in this SMB [5] had the same outer and inner diameters as those used in this study.…”
Section: Comparison With Previous Research Of the Restoring Force Alo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there are few superconducting magnetic bearings with and permanent magnet in the application of flywheel-based RBS at present. On the other hand, the attempts are currently underway to develop a superconducting magnetic bearing with high-temperature superconducting coils and bulks for flywheel-based RBS [41,42]. The public data showed that the superconducting magnetic bearing can provide a stable levitation of 158 kN, 7% over the target value, and its levitation force decrease was 1.3% for 8 h. It was reported that the levitation height of the flywheel can be kept constant by controlling the current applied to the superconducting coils if the flux creep characteristics are at this level [43].…”
Section: Flywheel Energy Storage (Fes)mentioning
confidence: 99%